If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x+7=-3x-11
We move all terms to the left:
15x+7-(-3x-11)=0
We get rid of parentheses
15x+3x+11+7=0
We add all the numbers together, and all the variables
18x+18=0
We move all terms containing x to the left, all other terms to the right
18x=-18
x=-18/18
x=-1
| 3x+31)=(2x-6 | | −35x=18−30−1045104530 | | 5(3x-7)=-2(7x+3) | | 0=4x^2-x-62 | | -16+18=-2(x+8) | | 5x-9=5x+11 | | 1/2(x+20)=14 | | |7h-10|=-4 | | m3.5=4.2 | | 17x+1=36x | | -2-4(2m-4)=10-8m | | -29=a-12 | | 12(x+20)=14 | | 0.4x+1.7=3.3 | | -106=-2(1+6m)-8 | | 8x−24+3x=6x+10 | | 7−13x=33 | | 2+5n=19 | | −0.1b=3.1 | | 10n+24=14n | | g+8(5-g)=89 | | 7m—2=8m+4—m | | 36-(1+2x)=-6(-7-2x) | | -10+y/2=-6 | | (4d+2)/4=2d+1 | | 110x+60=90x+100 | | 5x-10+33=9x+3 | | 15x+7=3x-11 | | 3x^2+-7=29 | | x=-x-10(-1.7x+0.4)-5.5 | | 3/420h−4)=8h−45 | | 2(2×+3)=x+9 |